Mountains and black races: anthropology’s heterotopias in colonial East Timor - Roque, Ricardo (2012)
This paper explores the pivotal status of mountain spaces in the 19th-century imaginary of wild peoples and black races in island Oceania. It adopts the notion of ‘heterotopia’ in order to examine how arrangements of human difference and spatial alterity were productively brought together in racial anthropology and in colonial praxis. Taking the example of the Portuguese former colony of East Timor, the author argues that anthropological theories of ‘mountain Negroes’, local categories of ‘mountain enemies’ and experiences of colonial hostility were mutually reinforcing.